Industry-based style investing - JAME, Russell (Institutional Knowledge at Singapore Management University, 2014)
Motivated by the style investing model of Barberis and Shleifer (2003), we examine the industry-wide investment decisions of retail investors. We find that retail investor industry demand is highly correlated and strongly related to past industry returns. Moreover, industries heavily bought by retail investors over the past year significantly underperform industries heavily sold over the subsequent year. Similarly, stocks in industries heavily bought by retail investors underperform stocks in industries heavily sold, even after controlling for firm-level demand. Our results suggest that industry-wide categorization influences the investment decisions of retail investors and has a significant impact on asset prices.